Occupying the crease : the influence of parents and coaches on New Zealand adolescent participation in cricket : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Management at Massey University - Gaskin, Cadeyrn James (Massey University, 2000)
The present study investigated whether the behaviours exhibited by parents and coaches had an influence on young cricketers' motives to participate in, or discontinue playing, cricket. Eight hundred and fifty-eight adolescent New Zealand cricketers completed a survey, which questioned them on their participation, or discontinuation, motives and their perceptions of the behaviours exhibited by their parents and coaches in relation to their participation in cricket. The results indicated that the behaviours of both parents and coaches were correlated with the participation/discontinuation motives of adolescent cricketers. Specifically, there was little difference in the associations between parental behaviour and both participation and discontinuation motivation, however, coaching behaviours were more strongly associated to the discontinuation motive than participation motives. This finding infers that coaches are a salient factor in young people's decisions to drop out of playing cricket. The analysis revealed multiple underlying motives for participating in cricket: team/enjoyment, achievement, affiliation, leisure/catharsis and skill/fitness. In addition, four categories of parental behaviour – supportive, criticising, interest in performance, and achievement focus - and three categories of coaching behaviour – supportive/instructional, punitive, and non-responsive – were identified. The relationships between participation motivation and both parental and coaching behaviours were similar to those between discontinuation motivation and the behaviours of parents and coaches. However, there were two exceptions: there was no association between both punitive and non-responsive coaching behaviours and participation motivation, and much stronger relationships between these two behaviours and discontinuation motivation. In conclusion, parents and coaches had an influence on the participation/discontinuation motives of adolescent cricketers in New Zealand through the behaviours they exhibited.
Keywords: Cricket (sport); Coaching; Young cricketers; Coach behaviour; Adolescent cricketers